Current Problems of Interaction between Emergency Medical Service and Population: Organizational, Financial, and Supply Chain management. - A. Zakharova; P. Zakharov (International Journal of Supply Chain Management, 2019)
At the current stage quality of emergency medical services (EMS) implies not only the professionalism of paramedics, but also the timeliness of their provision. The methods that allow for minimization of the patient’s waiting time for assistance are acquiring particular relevance. The purpose of this paper is to identify factors increasing the waiting time of EMS and prove the need to implement recommendations given on the reverse side of the first aid alert sheet for the citizens after calling an ambulance. The paper analyzes operation of Vladivostok EMS during 2016 – 2018 based on the data of the annual statistics report. In the process of solving these tasks of the thesis, the following research methods were used: analytical, descriptive, comparative, observation, simulation and generalization. nine ambulance crew shifts in Vladivostok city were studied with the help of observation and simulation methods. The results of this study were used as a basis for calculating time, which could be shortened in case if patients use our recommendations. The factors negatively affecting the delivery time of emergency medical service are drafted. The measures that can increase delivery of a quality medical service are offered. The developed recommendations can reduce time spent by an ambulance crew on the call, and improve efficiency of interaction between the ambulance crew and the patient.